Mapping Basic Motor Skills in Lower Grade Students: A Perspective from SDN 1 Betak - Bahrul Ngulum, Muhamat; Setiawan, Irwan; Husein Allsabah, M. Akbar (CV. Nusantara Sporta, 2024)
This study aims to analyze the basic motor skills of lower-grade students at SDN 1 Bertak. A descriptive quantitative method with a survey approach was used, measuring skills through Fundamental Movement Skills tests including 30-meter sprint, 4x10 meter shuttle-run, ball throwing and catching, and Stork Stand balance. Results indicate that most students possess motor skills in the good category, with variability in agility, balance, running speed, and hand-eye coordination. The study concludes that the basic motor skills of students at SDN 1 Bertak in 2023 are predominantly in the good category, with some areas needing improvement.